(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
A close reading to Pineda and Bascuñán’s Cautiverio Feliz, undoubtedly, would wake us a series of asociations, not only with other forms of historical literatura from the epoch, but also with other works that integrate some elements such as: kinds of speech structure and kinds of instrumental profiles. In this sense, reading Pineda`s work would lead us to Castiglione`s El Cortesano, because many of the characteristic of the perfect gentleman presented in El Cortesano, are inserted in some characters of Pineda`s work. It is not strange to find in El Cautiverio, among other things, the qualities of a perfect gentleman, shaped on the natives, virtues, virtues that also adorn some creole and old spaniards.